Effects of Plasmodium falciparum infection on umbilical artery resistance and intrafetal blood flow distribution: a Doppler ultrasound study from Papua New Guinea. (December 2017) - Ome-Kaius, Maria; Karl, Stephan; Wangnapi, Regina; Bolnga, John; Mola, Glen; Walker, Jane; Mueller, Ivo; Unger, Holger; Rogerson, Stephen
Abstract Background Doppler velocimetry studies of umbilical artery (UA) and middle cerebral artery (MCA) flow help to determine the presence and severity of fetal growth restriction. Increased UA resistance and reduced MCA pulsatility may indicate increased placental resistance and intrafetal blood flow redistribution. Malaria causes low birth weight and fetal growth restriction, but few studies have assessed its effects on uteroplacental and fetoplacental blood flow. Methods Colour-pulsed Doppler ultrasound was used to assess UA and MCA flow in 396 Papua New Guinean singleton fetuses. Abnormal flow was defined as an UA resistance index above the 90th centile, and/or a MCA pulsatility index and cerebroplacental ratio (ratio of MCA and UA pulsatility index) below the 10th centile of population-specific models fitted to the data. Associations between malaria (peripheral infection prior to and at ultrasound examination, and any gestational infection, i.e., 'exposure') and abnormal flow, and between abnormal flow and birth outcomes, were estimated. Results Of 78 malaria infection episodes detected before or at the ultrasound visit, 62 (79.5%) werePlasmodium falciparum (34 sub-microscopic infections), and 16 werePlasmodium vivax .Plasmodium falciparum infection before or at Doppler measurement was associated with increased UA resistance (adjusted odds ratio (aOR) 2.3 95% CI 1.0–5.2, P  = 0.047). When assessed by 'exposure', P. falciparum infection was significantly associated with increased UA resistance (all infections: 2.4, 1.1–4.9, P  = 0.024; sub-microscopic infections 2.6, 1.0–6.6, P  = 0.051) and a reduced MCA pulsatility index (all infections: 2.6, 1.2–5.3, P  = 0.012; sub-microscopic infections: 2.8, 1.1–7.5, P  = 0.035). Sub-microscopicP. falciparum infections were additionally associated with a reduced cerebroplacental ratio (3.64, 1.22–10.88, P  = 0.021). There were too fewP. vivax infections to draw robust conclusions. An increased UA resistance index was associated with histological evidence of placental malaria (5.1, 2.3–10.9, P  < 0.001; sensitivity 0.26, specificity 0.93). A low cerebroplacental Doppler ratio was associated with concurrently measuring small-for-gestational-age, and with low birth weight. Discussion/conclusion Both microscopic and sub-microscopicP. falciparum infections impair fetoplacental and intrafetal flow, at least temporarily. Increased UA resistance has high specificity but low sensitivity for the detection of placental infection. These findings suggest that interventions to protect the fetus should clear and prevent both microscopic and sub-microscopic malarial infections. Trial Registration ClinicalTrials.gov NCT01136850. Registered 06 April 2010